2022
DOI: 10.1186/s12916-022-02461-7
|View full text |Cite|
|
Sign up to set email alerts
|

Modified cardiovascular SOFA score in sepsis: development and internal and external validation

Abstract: Background The Sepsis-3 criteria introduced the system that uses the Sequential Organ-Failure Assessment (SOFA) score to define sepsis. The cardiovascular SOFA (CV SOFA) scoring system needs modification due to the change in guideline-recommended vasopressors. In this study, we aimed to develop and to validate the modified CV SOFA score. Methods We developed, internally validated, and externally validated the modified CV SOFA score using the suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In the previous study, we demonstrated that newly developed modified CV/total SOFA score had higher predictive validity and calibration in ED patients with suspected infection, sepsis, and septic shock. 20 In this study, the same concept was applied to ICU patients, and the prognostic performance of modified CV/total SOFA score is better than that of the original scoring system, consistent with previous study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the previous study, we demonstrated that newly developed modified CV/total SOFA score had higher predictive validity and calibration in ED patients with suspected infection, sepsis, and septic shock. 20 In this study, the same concept was applied to ICU patients, and the prognostic performance of modified CV/total SOFA score is better than that of the original scoring system, consistent with previous study.…”
Section: Discussionsupporting
confidence: 87%
“…With this background, we proposed the modified CV SOFA score using MAP, norepinephrine equivalent (NEq) dose ( Supplementary Table 1 ), and lactate in the previous multi-center, emergency department (ED) based study using suspected infection, sepsis, and septic shock cohorts. 20 We found that the modified CV/total SOFA score had better discrimination for 28-day mortality than the SOFA score and identified more patients at risk of septic mortality. In the present study, we externally validated the modified CV SOFA score in multi-center intensive care unit (ICU) patients with sepsis.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Sepsis is one of complications that seriously affect treatment success rate of patients admitted to intensive care unit(ICU) [1,2]. Patients suffering from sepsis are di cult to treat and have a high mortality rate.…”
Section: Introductionmentioning
confidence: 99%